The Effect of Good Corporate Governance on Company Performance with Corporate Social Responsibility as a Moderating Variable - Ahmad, Ibrahim; Amril, Amril; Yasen, Syahruddin; Machmud, Mulyana; Khalik, Abdul (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
The purpose of this study was to determine the effect of Good Corporate Governance on Company Performance with Corporate Social Responsibility as a Moderating Variable. This research is an Empirical Study of Manufacturing Companies Listed on the IDX for the 2017-2022 Period. The method used in this research is quantitative method. Empirical analysis can involve collecting company financial data, including Good Corporate Governance practices that may be measured by certain methods (such as accruals or other qualitative methods), as well as Company Performance data that can be calculated and Corporate Social Responsibility data as a Moderating Variable. After the data is collected, statistical analysis such as linear regression may be used to test the relationship between Good Corporate Governance variables on Company Performance With Corporate Social Responsibility As A Moderating Variable. The results of this study indicate that Good Corporate Governance practices have a negative effect on financial performance, Corporate Social Responsibility has a positive effect on financial performance, simultas Good Corporate Governance and Corporate Social Responsibility have a significant effect on financial performance.